Концепции космотеории (сообшение 8) - Суворов, Н.П.; Суворова, И.Г. (Медична гідрологія та реабілітація, 2008)
Дана публікація є продовженням викладу авторського погляду на стратегію розвитку людини. On basis of the powerinformation analysis the integrity approach in determination of major philosophical categories: progress, evolution, involutio (from Latin) and other have been developed.